2016
DOI: 10.1186/s12889-016-3443-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in sociodemographic characteristics, dietary behaviors and clinical parameters of adults receiving food assistance in France

Abstract: BackgroundIn 2004–2005, a survey carried out on food recipients in France revealed an alarming nutritional situation. In 2011–2012, and using a protocol similar to that of 2004–2005, our objective was to update the description of sociodemographic characteristics, dietary behaviors and clinical parameters of food assistance recipients and to analyze changes since 2004–2005.MethodsBoth surveys included multistage random sampling of adults benefitting from structures that supply food pantries and charitable groce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Additionally, lone parents may be at higher risk of financial strain as they are more likely to be unemployed (38) and to receive little or no social support from the absent parent (39). We found that the proportion of participants classified as food insecure is higher than for food aid users in other developed countries (40, 41), though it is comparable with the UK figures (9) We also found that food insecurity is prevalent outside foodbank settings, being higher than previously reported in the low-income British populations (29%) (10) and in inner London (20%) (42).…”
Section: Discussionsupporting
confidence: 71%
“…Additionally, lone parents may be at higher risk of financial strain as they are more likely to be unemployed (38) and to receive little or no social support from the absent parent (39). We found that the proportion of participants classified as food insecure is higher than for food aid users in other developed countries (40, 41), though it is comparable with the UK figures (9) We also found that food insecurity is prevalent outside foodbank settings, being higher than previously reported in the low-income British populations (29%) (10) and in inner London (20%) (42).…”
Section: Discussionsupporting
confidence: 71%
“…The results add to the limited evidence that FI is also highly prevalent in affluent European countries ( Neter et al, 2014 , Power et al, 2017 ). A comparison with FI prevalence rates of food bank users in other countries showed lower rates among food bank users in Germany compared to food bank users in the Netherlands ( Neter et al, 2014 ), France ( Castetbon et al, 2016 ), the U.S. or Canada ( Tarasuk and Beaton, 1999 ; Robaina and Martin, 2013 ; Leung et al, 2015 ). Both Dutch and French food banks provide food parcels that supplement the participants' diet while German food banks allow food bank users to choose available, mainly fresh foods.…”
Section: Discussionmentioning
confidence: 97%
“…However, this study is its first in Germany and one of only a few studies examining FI in European countries ( Castetbon et al, 2016 ; Neter et al, 2014 ; Power et al, 2017 ). Another strength of this study is the large number of participants from three different German cities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is one of the most critical factors for chronic diseases such as cardiovascular disease, stroke, arrhythmias, heart failure, and renal disease[ 1 ] which is defined as a systolic blood pressure of 140 mmHg or more and a diastolic blood pressure of 90 mmHg or more[ 2 3 ] and is the first factor of premature death and failure among all causes of death in the world. [ 4 ] It is a common disease without any symptoms, and a person may have hypertension for years without knowing that he/she has a blood pressure. [ 5 ] Recent studies have estimated the general prevalence of hypertension in Iran by 22%, and evidence suggests a growing trend in Iran.…”
Section: Introductionmentioning
confidence: 99%